1994
DOI: 10.1002/hlca.19940770509
|View full text |Cite
|
Sign up to set email alerts
|

Nucleosides. Part LVI. Aminolysis of carbamates of adenosine and cytidine

Abstract: The 2-(4-nitrophenyl)ethoxycarbonyl (npeoc) group, introduced 1984 as protecting group for exocyclic amino functions of nucleic-acid bases, reacts with amines under mild conditions to urea derivatives. Treatment of 2',5'-di-0-acetyl-N6-[2-(4-nitrophenyl)ethoxycarbony~]cordycepin (3) with NHJMeOH overnight at room temperature affords cordycepin (4) and N6-carbamoylcordycepin (5). Preliminary investigations towards the elucidation of the reaction mechanism indicate that the aminolysis proceeds via an addition-el… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
5
0

Year Published

1994
1994
2014
2014

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(5 citation statements)
references
References 38 publications
0
5
0
Order By: Relevance
“…The phenoxycarbonyl group was selectively introduced to the 4-amino function of deoxycytidine by the transient protection method using trimethylsilyl chloride. [22,23] Subsequently, the 4-N-(phenoxycarbonyl)deoxycytidine intermediate 6 was converted into various 4-N-carbamoyldeoxycytidine derivatives 1a-e by treatment with the corresponding amines followed by removal of the trimethylsilyl groups. Treatment of 1a-e with DMTrCl gave the 5Ј-O-dimethoxytritylated products 7a-e.…”
Section: Synthesis Of 4-n-carbamoyldeoxycytidine Derivativesmentioning
confidence: 99%
“…The phenoxycarbonyl group was selectively introduced to the 4-amino function of deoxycytidine by the transient protection method using trimethylsilyl chloride. [22,23] Subsequently, the 4-N-(phenoxycarbonyl)deoxycytidine intermediate 6 was converted into various 4-N-carbamoyldeoxycytidine derivatives 1a-e by treatment with the corresponding amines followed by removal of the trimethylsilyl groups. Treatment of 1a-e with DMTrCl gave the 5Ј-O-dimethoxytritylated products 7a-e.…”
Section: Synthesis Of 4-n-carbamoyldeoxycytidine Derivativesmentioning
confidence: 99%
“…The subsequent protection of the 6-NH 2 -(methoxycarbonyl) group [34] forming 19 as a by-product. Finally, the required building block 22 resulted from subsequent reactions involving selective monomethoxytritylation of the 5'-OH group of 18 ( 3 20; 88%), then introduction of the (tert-butyl)dimethylsilyl (tbdms) group at the 2'-OH position ( 3 21; 95%), followed by treatment with 2% TsOH in CH 2 Cl 2 /MeOH 4:1 to cleave off the MeOTr group ( 3 22; 89%).…”
mentioning
confidence: 99%
“…The acidic function of CdU 2 has to be protected prior to the chemical incorporation of 2 into DNA fragments. In addition, the presence of the carboxylic group requires that the concentrated aqueous solution of ammonia is substituted by a solution of 0.2 N NaOH/MeOH, , in order to avoid the formation of an amide function during the deprotection step involving alkali treatment . The ethyl group was chosen for the protection of the carboxylic acid function with regard to the work of Bender on the hydrolysis kinetic of benzoic acid esters in NaOH.…”
mentioning
confidence: 99%
“…In addition, the presence of the carboxylic group requires that the concentrated aqueous solution of ammonia is substituted by a solution of 0.2 N NaOH/MeOH, 8,9 in order to avoid the formation of an amide function during the deprotection step involving alkali treatment. 10 The ethyl group was chosen for the protection of the carboxylic acid function with regard to the work of Bender 11 on the hydrolysis kinetic of benzoic acid esters in NaOH. This author showed that the rate constant of hydrolysis of ethyl benzoate was similar to that of the half-life 2-isobutyryl-2′-deoxyguanosine 8 (271 min) under the latter conditions.…”
mentioning
confidence: 99%